Conceptions of Learning and Teaching and Their Relation to Educational Variables During Teaching Second Language - Tim Chen; Robert C. Crosbie; Azita Anandkumarb; Charles Melville; N Nguyen; J Chen (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background:  People who choose to study a second language like English face an emotional charge that affects directly to the learning process. Regarding the writing production, learners create short compositions about specific topics with instructions based on grammatical structures. Once it is done, learners receive feedback on their work. However, some learners do not want to write any text because the teacher puts more attention to their mistakes rather than their successes. Without taking into account their needs, topics of interest or motivation for carrying out the exercise Contribution:  Therefore, it is set to identify the emotions that are generated by the corrections made to our learners’ written work. Method:  The research was carried on with university students aged between 18 and 25 years old who are attending classes at the center of university language classroom. This research during the April- August 2016 term. Results: It has been found that the emotions (positive and negative) play an important role or have a great impact that causes aversion towards language learning. Therefore, it is necessary that teachers provide adequate feedback for language learning. Conclusion:  Corrections generate aversion towards the learning process. Regarding the feedback students receive from their teachers, it generates emotional charge (positive and negative) which should be followed